Perlindungan Hukum Hak Pemegang Saham Dalam Pembubaran Perusahaan Berdasarkan Undang-Undang Nomor 40 Tahun 2007 - Diyan Ibaidah Ayogi; Chusnia Chusnia; Sumriyah Sumriyah (Jurnal Hukum dan Sosial Politik, 2023)
Company dissolution and legal protection of shareholder rights are regulated based on Law Number 40 of 2007 concerning Limited Liability Companies in Indonesia. The journal discusses the procedure for dissolving a company, the reasons for dissolving, and options for filing a lawsuit against the court for dissolving a company when a dispute arises between shareholders. The author emphasizes the importance of legal protection for shareholders and the need for clear regulations in the Indonesian Limited Liability Company Law. Normative legal research methods (normative legal research). The results of this study indicate that the procedure for dissolving a company based on Law Number 40 of 2007 concerning limited liability companies can apply for the dissolution of a company through a district court. There are shareholder rights that must be protected and shareholders must exercise their rights through adequate procedures that have been determined by the company.